Per una teoria generale dei diritti digitali - Federico Oliveri (Democrazia e Diritti Sociali)
This essay proposes, within the theoretical-legal framework of a democratic digital constitutionalism, a ‘logical genesis’ of digital rights. The approach identified makes it possible to develop a systematic reconstruction of the different families of digital rights, each of which responds to specific ‘constituent functions’ required by a democratic governance of digital environments. With respect to the current debate, the essay intends to arrive at a systematic vision of digital rights, capable of responding both to the protection needs that have matured in the network environment and to those that have emerged in relation to the latest generation of artificial intelligence systems. This is a theoretical reconstruction, which is critical with respect to the digital law that actually exists, and programmatic with respect to future digital law. In conclusion, we recall the necessary link between this reconstruction and the claims of the stakeholders, so that the theoretical-critical instances find their way to practical realisation.